Fresh state properties of concrete incorporating scrap tire rubber - Medine, M. (2016)
The purpose of this work is to study fresh lightweight concrete containing recycled tire rubber aggregates. An experiment on concrete obtained by incorporating rubber aggregate with a ratio replacement of 5, 7.5 and 10% is done to evaluate the effect of these aggregates on the workability of two sets of concrete specimens. In the first set, coarse aggregates were replaced by different percentages by weight of granulate rubber and in the second set both coarse aggregates and sand were replaced rubber granulate and crumb rubber. Density, air content, compaction and slump tests are performed on the seven mixtures. Taking into account the density and water absorption differences between the natural aggregates and the rubber aggregates, the validity of the tests results are discussed. The results show that incorporating these rubber aggregates affects most rheological properties of lightweight concrete, for some application of concrete incorporating waste tire, rubber particles should be treated.